The scavenging capacity of γ-aminobutyric acid for acrolein and the cytotoxicity of the formed adduct. Issue 9 (14th August 2020) - Jiang, Kaiyu; Yin, Zhao; Zhou, Ping; Guo, Hongyang; Huang, Caihuang; Zhang, Guangwen; Hu, Wenzhong; Ou, Shiyi; Ou, Juanying
Abstract : Acrolein is a notorious aldehyde with hazardous impacts on humans. Abstract : Acrolein is a notorious aldehyde with hazardous impacts on humans. γ-Aminobutyric acid (GABA) is a functional amino acid present widely in foods. This study aimed at investigating the protective mechanism of GABA against acrolein. In simulated physiological and thermal processing models, GABA effectively scavenged acrolein by adduct formation. The cytotoxicity of the formed adduct was evaluated in human bronchial epithelial cell line HBE and normal colonic epithelial cell line NCM460. It tremendously decreased acrolein toxicity and exerted protective effects by ROS reduction. Apoptotic staining and signaling analysis showed that it also interfered with apoptosis via extrinsic and intrinsic pathways. Our findings provide the basic knowledge that GABA is an effective acrolein scavenger and it has potential detoxifying capacity for both exogenous and endogenous acrolein sourced cellular damage.